2019
DOI: 10.5551/jat.45799
|View full text |Cite
|
Sign up to set email alerts
|

Bezafibrate Ameliorates Arterial Stiffness Assessed by Cardio-Ankle Vascular Index in Hypertriglyceridemic Patients with Type 2 Diabetes Mellitus

Abstract: Aim: Cardio-ankle vascular index (CAVI) reflects arterial stiffness and has been established as a useful surrogate marker of atherosclerosis. Contrary to the abundant data indicating slower progression of atherosclerosis with statins, studies on fibrates remain scarce. The aim of this study was thus to clarify the effect of bezafibrate on CAVI as well as on oxidative stress. Methods: A randomized, open-label, controlled study was performed. 66 hypertriglyceridemic patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…This suggested that serial assessments of arterial stiffness using CAVI could serve as an indicator of the need for treatment. Moreover, several interventional studies showed that nonpharmacological and pharmacological treatments were associated with an improvement in CAVI 27 29 ) . To determine the utility of CAVI in patients with ACS, more clinical and experimental studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…This suggested that serial assessments of arterial stiffness using CAVI could serve as an indicator of the need for treatment. Moreover, several interventional studies showed that nonpharmacological and pharmacological treatments were associated with an improvement in CAVI 27 29 ) . To determine the utility of CAVI in patients with ACS, more clinical and experimental studies are required.…”
Section: Discussionmentioning
confidence: 99%
“…Eicosapentaenoic acid decreases CAVI together with a reduction in oxidized LDL 71 ) . Yamaguchi et al 72 ) reported that bezafibrate ameliorates CAVI accompanied by improvement of remnant-like particle cholesterol and diacron-reactive oxygen metabolites. In patients with dyslipidemia, coexisting abnormal glycolipid metabolism and oxidative stress may affect CAVI.…”
Section: Various Factors Affecting Cavi (Cross-sectional Studies)mentioning
confidence: 99%
“…Plasma triglyceride levels have recently garnered considerable attention as a residual risk for cardiovascular events 17) . Clinical studies have demonstrated that treatment with fibrates reduces cardiovascular events associated with hypertriglyceridemia [18][19][20][21] . Yet there are several limitations concerning the use of fibrates 22) ; for example, their activity on PPAR is relatively weak, and their efficacy depends on the targeted population.…”
Section: Introductionmentioning
confidence: 99%